Effect of cutting speed on cutting torque and cutting power of varying kenaf-stem diameters at different moisture contents - Musa, Dauda Solomon; Ahmad, Desa; Abdan, Khalina; Othman, Jamarei (Universiti Putra Malaysia Press, 2015)
This study focused on the development of an efficient cutting system for kenaf harvesters. Laboratory experiments were conducted on cutting kenaf stems of variety V36 using a rotary serrated cutting system. The Torque Trak 10k data acquisition system was used for the experiment. The effect of cutting speed on cutting torque and cutting power of varying kenaf-stem diameters and at different moisture contents was investigated. Four different cutting speeds of 400 rpm, 500 rpm, 600 rpm and 700 rpm were used. The experiments showed that cutting speed had significant effect on cutting torque and cutting power requirements. The cutting speed was directly proportional to the specific cutting power, while the cutting torque was inversely proportional to the moisture content. Increasing the rotational speed from 400 rpm to 700 rpm reduced the cutting torque from 1.91 Nm to 1.49 Nm. The cutting torque was observed to be higher at lower moisture levels of less than 35%. As the moisture content was increased to values greater than 35%, the torque decreased considerably. This invariably indicated that an increase in moisture content reduced cutting torque as shown by the model coefficient of moisture content. Thus, more energy saving and hence, high efficiency, were achieved at high cutting speeds as compared to impact cutting system at similar speeds. Regression equations capable of predicting cutting torque and cutting power at varying stem diameters and cutting speeds, in relation to kenaf stem moisture contents, are presented.